Genome‐wide postnatal changes in immunity following fetal inflammatory response. (24th October 2020) - Costa, Daniel; Bonet, Núria; Solé, Amanda; González de Aledo‐Castillo, José Manuel; Sabidó, Eduard; Casals, Ferran; Rovira, Carlota; Nadal, Alfons; Marin, Jose Luis; Cobo, Teresa; Castelo, Robert
Abstract : The fetal inflammatory response (FIR) increases the risk of perinatal brain injury, particularly in extremely low gestational age newborns (ELGANs, < 28 weeks of gestation). One of the mechanisms contributing to such a risk is a postnatal intermittent or sustained systemic inflammation (ISSI) following FIR. The link between prenatal and postnatal systemic inflammation is supported by the presence of well‐established inflammatory biomarkers in the umbilical cord and peripheral blood. However, the extent of molecular changes contributing to this association is unknown. Using RNA sequencing and mass spectrometry proteomics, we profiled the transcriptome and proteome of archived neonatal dried blood spot (DBS) specimens from 21 ELGANs. Comparing FIR‐affected and unaffected ELGANs, we identified 782 gene and 27 protein expression changes of 50% magnitude or more, and an experiment‐wide significance level below 5% false discovery rate. These expression changes confirm the robust postnatal activation of the innate immune system in FIR‐affected ELGANs and reveal for the first time an impairment of their adaptive immunity. In turn, the altered pathways provide clues about the molecular mechanisms triggering ISSI after FIR, and the onset of perinatal brain injury. Databases: EGAS00001003635 (EGA); PXD011626 (PRIDE). Abstract : The exposure to a fetal inflammatory response (FIR) is often followed by a postnatal systemic inflammation, increasing the risk of perinatal brain injury. We profiled the transcriptome and proteome in neonatal dried blood spots from extremely preterm newborns (< 28 weeks of gestation), affected and unaffected by FIR. The observed molecular changes confirm the activation of the innate immune system in FIR‐affected neonates and reveal an impairment of their adaptive immunity.